The Impact of Advanced Technology on Indonesia’s National Security Stability - Pratiwi, Amelia Chandra; Tarigan, Herlina (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
In the current era of ever-growing globalization, technological progress has become one of the main pillars in changing the perspective of human life. Apart from that, cyber security is also one of the main pillars in efforts to develop Indonesia's digital economy. This study aims to examine the positive and negative impact of advanced technology on Indonesia's National Security Stability. The method used is a descriptive research method carried out qualitatively. This study formulated the efforts that can be taken to maintain the stability of the Indonesian defense and security system in facing the negative impacts of technological developments. Several efforts that can help face the negative impacts of technological developments are the development of cyber defense capabilities, strengthening security and data protection, diversification and strengthening of Human Resources, collaboration with the private sector and universities, and strict supervision and control system. Some of these things must be implemented with continuous commitment and efforts so that Indonesia’s defense and security capabilities can be very resilient and be able very resilient and will continue to grow and get stronger in the future.